STUDENTS’ STANDPOINT: USING DEBATE IN A CRITICAL AND ANALYTICAL SPEAKING CLASS - Dewi Rosaria Indah (Magister Scientiae, 2021)
This study presents a description of how the students were involved in an academic debate format for the Critical and Analytical Speaking class. The nature of this study was qualitative descriptive which used online questionnaires to the students from batch 2016 to 2018. It was found that the students initially had some anxiety for having to speak in English, let alone in the context of debate. They stated that the debate in the speaking class was exciting and challenging. Also, it was said that the class was able to enhance their speaking skill because it encouraged them to think critically, to be open minded, as they found and sorted ideas, knowledge and facts; an example of this was when then expressed their convincing arguments to tackle opponents’ standpoint. They admitted that they preferred to be in the contra side that was generally against the norms, open for possibilities to bend rules by questioning the law or contradicting society’s points of view.